Assessing the Link Between Intimate Partner Violence and Postrelationship Stalking: A Gender-Inclusive Study - Senkans, Svenja (Journal of interpersonal violence, 2021)
The link between intimate partner violence (IPV) during a relationship and postrelationship stalking (PRS) is poorly understood. The vast majority of relevant studies focus either on male perpetration or female victimization and use highly selective samples. The current study aimed to illuminate the link between IPV and PRS perpetration and victimization, respectively. To this end, heterosexual male and female university students (n = 422) retrospectively self-reported on IPV during their most conflicted relationship and a wide range of pursuit behavior after the dissolution of this romantic relationship. Using empirical criteria, participants were classified as stalkers or nonstalkers based on their responses. A relationship between male-perpetrated IPV and PRS perpetration was detected. There was no systematic relationship between IPV and PRS perpetration in women. In contrast, there was a link between IPV and stalking victimization that followed a similar, linear trend in both male and female victims. A larger proportion of participants were classified as stalking victims as IPV severity increased. Implications for research (e.g., the importance of gender-inclusive studies), clinical practice (e.g., how to prevent stalking after an abusive relationship), and future directions (e.g., the need for prospective studies using more diverse samples) are discussed.